ISO 21500: How project management standard can contribute to a consultancy firm in Iceland - Lára Kristín Kristinsdóttir 1983- (2014)
Viðskiptafræðideild hefur samþykkt lokaðan aðgang að þessari ritgerð í tvö ár. The objective of the dissertation is to see how ISO 21500 can benefit a consultancy firm in Iceland that has already been certified for several ISO standards. To answer this question a qualitative research was conducted to see how employees from a certain company worked with processes in regards to the projects they were partaking in and what views they had concerning their environment and management. The aim was to see how the employees viewed processes like documentation, risk management and other important factors, what they thought could be improved and what they believed was an obstacle in achieving a more optimum way of working. This was done to understand how the situation was before applying ISO 21500 to the company and to see if there would be any benefits of incorporating the standard. The results show that the standard can benefit companies even though they have several other ISO certifications. One of the greatest benefits for this company was common process for all projects where employees and managers synchronize their work and minimize shortcomings. The second benefit was better management of communication and documentation where stable and stronger processes were needed. The third benefit was the possibility of increased solidarity where clearer boundaries and expectations were set in place for a better teamwork. The last benefit that will be mentioned, even though there are great many more, is quality. The standard gives the company the opportunity to evaluate the kinds of work procedures they want to incorporate and what kind of quality they would want their customers to receive.